2022
DOI: 10.1111/1753-6405.13199
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported wellbeing and health‐related quality of life of Aboriginal and Torres Strait Islander people pre and post the first wave of the COVID‐19 2020 pandemic

Abstract: Objective: Quantify change in wellbeing and health-related quality-of-life (HRQoL) in Aboriginal and Torres Strait Islander adults pre and post Australia's initial COVID-19 lockdown.Methods: Aboriginal and Torres Strait Islander adults completed an online survey at Time 1 (October-November 2019; before the initial Australian COVID-19 outbreak) and Time 2 (August-September 2020; after the first Australian lockdown). We assessed wellbeing using a visual analogue scale (VAS) and HRQoL using the Assessment of Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Out of these financial factors, income change is the most significant, regardless of the control factor used. Our results are in line with previous research conducted by Gall et al [ 28 ] who showed that mean reduction in well-being was associated with financial instability and mental health comorbidity. Also, VanderWeele et al [ 80 ] showed in the USA how well-being has declined before and during the COVID-19 in terms of financial stability, happiness and health.…”
Section: Resultssupporting
confidence: 93%
“…Out of these financial factors, income change is the most significant, regardless of the control factor used. Our results are in line with previous research conducted by Gall et al [ 28 ] who showed that mean reduction in well-being was associated with financial instability and mental health comorbidity. Also, VanderWeele et al [ 80 ] showed in the USA how well-being has declined before and during the COVID-19 in terms of financial stability, happiness and health.…”
Section: Resultssupporting
confidence: 93%
“…Some of these patterns indicate there are probably within-group differences within Aboriginal and Torres Strait Islander peoples that could explain some of these inconsistencies in changes over time. Understanding these within-group differences is important from a policy perspective, with previous research highlighting how age, financial instability, and mental health comorbidity influenced self-reported health outcomes prepandemic and during the pandemic ( 16 ). One of the limitations of this study was the small sample size of Aboriginal and Torres Strait Islander peoples, which did not permit an intersectionality analysis of different demographic groupings within this community.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the risk factors for reduced scores on the wellbeing scales included being female, of a younger age, and having a mental health condition ( 12 , 14 16 , 18 ). Factors related to higher scores on the wellbeing scales included older age and financial stability ( 12 , 16 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations